Investigation of the Histology and Some Histochemical Properties of the Gastrointestinal Canal of Mastacembelus mastacembelus (Banks & Solander, 1794) - Karataş, Halit; Köprücü, Sibel (Durmuş Ali ARSLAN, 2024)
The study investigated the histological and histochemical characteristics of the digestive tract of five specimens of Mastacembelus mastacembelus (Banks & Solander, 1794) specimens caught from the Keban Dam Lake in Elazığ. It has been determined that the stomach of Mastacembelus mastacembelus consists of three regions: cardiac, fundus, and pyloric. Each region contains the layers of tunica mucosa, submucosa, tunica muscularis, and tunica serosa. The mucosal layer is observed to be convoluted and composed of prismatic cells. Gastric glands are present in the cardiac and fundus regions, but they are absent in the pyloric region. Longitudinal and circular muscle layers, and tunica serosa layers were identified in all stomach sections. Histochemical staining results showed that the glucoconjugates in the mucus cells showed a variable degree of reaction. The intestines of Mastacembelus mastacembelus were examined in three sections: the thin, medium, and thick intestines. In each section, the layers of tunica mucosa, submucosa, tunica muscularis, and tunica serosa were identified, with the mucosa consisting of prismatic epithelial cells and containing a large number of goblet cells. The tunica muscularis, consisting of longitudinal and circular muscle fibres, and the tunica serosa consisting of connective tissue, were also observed. Histochemical staining studies showed that acidic glucoconjugates were more abundant in goblet cells than neutral glucoconjugates.

Araştırmada Elazığ Keban Baraj Gölü’nden avlanan 5 adet Mastacembelus mastacembelus (Banks & Solander, 1794)’un sindirim kanalının histolojik ve histokimyasal özellikleri araştırıldı. Mastacembelus mastacembelus'un midesinin kardiak, fundus ve pilorik olmak üzere üç bölümden oluştuğu, her bölümde tunika mukoza, submukoza, tunika muskularis ve tunika serosa tabakalarının bulunduğu tespit edilmiştir. Mukoza tabakasının kıvrımlı yapıda olup prizmatik hücrelerden oluştuğu, kardiak ve fundus bölgelerinde gastrik bezler bulunurken pilorik bölgede bu bezlerin yer almadığı gözlenmiştir. Tüm mide bölümlerinde longitudal ve sirküler kas katmanları ile tunika serosa tabakaları tespit edilmiştir. Histokimyasal boyamalar sonucunda, mukus hücrelerindeki glukokonjugatların farklı derecelerde reaksiyon gösterdiği belirlenmiştir. Mastacembelus mastacembelus'un bağırsakları, ince, orta ve kalın olmak üzere üç bölümde incelenmiştir. Her bölümde, içten dışa doğru tunika mukoza, submukoza, tunika muskularis ve tunika serosa tabakalarının bulunduğu, mukozanın prizmatik epitel hücrelerinden oluştuğu ve bol miktarda goblet hücresi içerdiği gözlemlenmiştir. Longitudinal ve sirküler kas fibrillerinden oluşan tunika muskularis ile bağ dokusundan meydana gelen tunika serosa tabakaları da tespit edilmiştir. Histokimyasal boyama çalışmaları sonucunda, goblet hücrelerinde asidik glukokonjugatların, nötral glukokonjugatlara göre daha baskın olduğu belirlenmiştir.
Mastacembelus mastacembelus, Bank Ve Solander, 1794, un Sindirim Kanalının Histolojisi ve Bazı Histokimyasal Özelliklerinin Araştırılması
Keywords: Aquaculture and Fisheries (Other); Sucul Kültür ve Balıkçılık (Diğer)